A bibliometric analysis of ginger's anticancer potential: bioactive compounds, cancer types, and mechanisms of action - Maharani, Putu Audi Mas; Sarmoko (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2024)
This study explores the anticancer properties of ginger (Zingiber officinale) through comprehensive bibliometric analysis of literature published from 2015 to 2024. Using PRISMA methodology, 49 relevant articles were identified from PubMed and analyzed through Biblioshiny and VOSviewer software. The International Journal of Molecular Sciences emerged as the leading publication source. Network visualization identified three major research clusters: antioxidant mechanisms, cancer biology, and phytochemical applications. Triple-negative breast cancer and colorectal cancer represent the most extensively studied malignancies. Mechanistically, ginger compounds (particularly gingerols and shogaols) demonstrate anticancer effects through multiple pathways including apoptosis induction, cell cycle arrest, anti-metastatic activity, oxidative stress modulation, and angiogenesis inhibition. While in vitro and preclinical evidence is robust, clinical translation remains limited. This analysis provides a comprehensive overview of ginger's anticancer research landscape, highlighting established mechanisms, identifying knowledge gaps, and suggesting future directions. The findings support ginger's potential as a complementary therapeutic agent and source of lead compounds for anticancer drug development, while emphasizing the need for advanced clinical investigations.